2006
DOI: 10.2320/matertrans.47.287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Addition on Microstructure and Mechanical Properties of a Wrought Co–Cr–Mo Implant Alloy

Abstract: The wrought Co-Cr-Mo alloys with C contents of 0.02, 0.09 and 0.18% (mass%) were fabricated by hot-forging process to study the influence of carbon contents on the microstructures and mechanical properties. The microstructures of Co-29Cr-6Mo-0.02C and Co-29Cr-6Mo-0.09C consist of equiaxed uniform grains which contain stacking faults, twins and " martensite bands. No carbide found at inter-and intragranular region. Co-29Cr-6Mo-0.18C consists of irregular grain sizes and carbide found at inter-and intra-granular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 16 publications
6
37
0
2
Order By: Relevance
“…19.10b): it increased initially, peaking at~0.1 mass% C, and then gradually decreased with further increase in carbon concentration. Similar results were reported for Co-CrMo-based alloys [19]. Figure 19.11 shows typical fracture surfaces of the tensile-tested specimens of the as-cast and hot-rolled alloys with high carbon content.…”
Section: Effect Of Carbon Concentration On Tensilesupporting
confidence: 72%
See 1 more Smart Citation
“…19.10b): it increased initially, peaking at~0.1 mass% C, and then gradually decreased with further increase in carbon concentration. Similar results were reported for Co-CrMo-based alloys [19]. Figure 19.11 shows typical fracture surfaces of the tensile-tested specimens of the as-cast and hot-rolled alloys with high carbon content.…”
Section: Effect Of Carbon Concentration On Tensilesupporting
confidence: 72%
“…Our previous studies [9,19] showed that solid-solution strengthening of carbon was negligible, as theoretically predicted; therefore, the precipitates would have 1 The casting and hot-rolling conditions are the same as those described in the previous sections. [11,12] dominated the strengthening of the present alloys.…”
Section: Effect Of Carbon Concentration On Tensilementioning
confidence: 99%
“…5,6) It was reported that under the ascast condition, Ni-, C-and N-free Co-Cr-Mo alloys exhibit low ductility owing to the formation of shrinkage porosity, interdendritic segregation, and intermetallic inclusions at the grain boundaries. 7) Especially, the phase formed along the interdendritic region during the solidification gives rise to brittle fracture. 7) Thus, it is essential to suppress the formation of the phase in the as-cast Co-Cr-Mo alloys to improve the ductility.…”
Section: Introductionmentioning
confidence: 99%
“…7) Especially, the phase formed along the interdendritic region during the solidification gives rise to brittle fracture. 7) Thus, it is essential to suppress the formation of the phase in the as-cast Co-Cr-Mo alloys to improve the ductility. Therefore, a number of studies on chemical composition and casting technology have been tried in order to improve the strength and ductility of these alloys.…”
Section: Introductionmentioning
confidence: 99%
“…4) From the above properties, it can be summarized that the alloy consisting of the phase is favorable for plastic forming and the alloy consisting of the " phase is promising for the application used in corrosion or wear circumstance. Although the effect of heat treatment and carbon addition on the stability of phase have been reported so far, 5) the stability of the " phase has not been investigated in detail yet. Figure 1 shows the ternary phase diagrams of Co-Cr-Mo alloy system 6) at (a) 1473 K and (b) 1200 K. The solid circles in the Fig.…”
Section: Introductionmentioning
confidence: 99%